Panax notoginseng: derived exosome-like nanoparticles attenuate ischemia reperfusion injury via altering microglia polarization - Shiyi Li; Ru Zhang; Anni Wang; Yang Li; Miaomiao Zhang; Jisu Kim; Ying Zhu; Qizheng Wang; Yue Zhang; Ying Wei; Jianxin Wang (Journal of Nanobiotechnology, 2023)
Abstract Cerebral ischemia/reperfusion (CI/R) injury is a clinical conundrum during the treatment of ischemic stroke. Cell-derived exosomes (CDE) were proved to be therapeutically effective for CI/R injury. However, production of CDE is time and effort consuming. Increasing studies reported that plants can also generate exosome-like nanoparticles (ELN) which are therapeutically effective and have higher yield compared with CDE. In this study, a commonly used Chinese herb Panax notoginseng (PN), whose active ingredients were well-documented in the treatment of CI/R injury, was chosen as a source of ELNs. It was found that Panax notoginseng derived exosome like nanoparticles (PDN) could enter the brain without modification and ameliorate cerebral infarct volume, improve behavior outcome and maintained the integrity of BBB. PDNs attenuated CI/R injury by altering the phenotype of microglia from “pro-inflammation” M1 type to “anti-inflammation” M2 type. Also, we found that lipids from PDNs were the major therapeutic effective component. As a mechanism of action, PDN was proved to exert therapeutic effect via activating pI3k/Akt pathway. Graphical Abstract